Comparación entre ecuaciones para estimar el requerimiento energético en mujeres antioqueñas con exceso de peso (Colombia) (2018)
ABSTRACT: The Energy Expenditure (EE) is the sum of the Basal Metabolic Rate (BMR), Endogenous Thermogenesis (ET) and the Physical Activity (PA). The indirect calorimetric (IC) is one of the methods used to measure the EE in the human beings; however, there are more than 200 equations to estimate it. Objective: To compare the EE using the IC with some of the most used equations to estimate the EE at rest. Materials and Methods: There were selected 1,178 women between 18 and 73, with overweight, who assisted during 9 years (2006-2015) to private medical consultation. Statistical Analysis: It was carried out a descriptive-comparative analysis of cross-section multidimensional type. For the statistical analysis, it was used the GENERALIZED LINEAR MODEL, furthermore, it was applied unidimensional descriptive statistics. SAS University program was employed. Results: In the current investigation it was proven that as the age increases the height decreases and the average weight and BMI increases. By carrying out the statistical analysis, it was not detected any significant difference in the EE determined by the IC between the analyzed groups (p>0.05). It was detected a significant difference (p<0.05) in the EE, according to the Harris Benedict (HB) equation, among young people. Conclusion: After the general analysis of all the groups was carriedout, it was found that the Mifflin-St.Jeor equation significantly determined a lower EE, while the EE obtained by the Empirical formulas P2 and P3 (25 and 30 kcal / kg / day respectively) were significantly higher in all groups; however the behavior of the EE was similar with the equations FAO- OMS, HB, P1 (20 kcals / kg / day) and CI.